2007
DOI: 10.1097/wnr.0b013e3282f213e0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of Notch signaling in the mature guinea pig cochlea

Abstract: Recent studies using explant cultures have demonstrated that pharmacological inhibition of Notch signaling by gamma-secretase inhibitors generates supernumerary hair cells in embryonic or neonatal cochleae. The aim of this study was to examine the effects of such pharmacological inhibition on mature auditory epithelia in vivo. Normal adult guinea pig auditory epithelia exhibited weak or no immunoreactivity for Notch1 and Jagged1, whereas ototoxic treatment caused the upregulation of these molecules in damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 16 publications
5
57
0
Order By: Relevance
“…A growing number of studies have explored how the manipulation of Notch signaling could aid in regenerating mammalian hair cells. It is well established that the inhibition of Notch signaling causes an increase in the number of hair cells in uninjured and injured chicken, guinea pig, and mouse utricles and cochleae and in injured zebrafish ears and lateral line neuromasts (52,53,(55)(56)(57)88). The presence of Notch is detrimental to hair cell differentiation, because it blocks the proneural gene atoh1a and thereby maintains support cells (9,13,65,89,90).…”
Section: Notch Signaling Is Down-regulated Early In Lateral Line Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have explored how the manipulation of Notch signaling could aid in regenerating mammalian hair cells. It is well established that the inhibition of Notch signaling causes an increase in the number of hair cells in uninjured and injured chicken, guinea pig, and mouse utricles and cochleae and in injured zebrafish ears and lateral line neuromasts (52,53,(55)(56)(57)88). The presence of Notch is detrimental to hair cell differentiation, because it blocks the proneural gene atoh1a and thereby maintains support cells (9,13,65,89,90).…”
Section: Notch Signaling Is Down-regulated Early In Lateral Line Hairmentioning
confidence: 99%
“…It has not been appreciated previously that the down-regulation of Notch signaling could be a hallmark of spontaneously regenerating sensory epithelia, because it was reported that the Notch signaling pathway is up-regulated in response to hair cell death in chicken, guinea pigs, and zebrafish (9,88,98). However, these expression analyses were performed at later time points during the regeneration process, when Notch signaling is required once again for hair cell versus support cell specification to occur.…”
Section: Notch Signaling Is Down-regulated Early In Lateral Line Hairmentioning
confidence: 99%
“…Recently, a similar result was reported for a mammalian ear. Notch signaling components were found to be upregulated in the epithelia of adult guinea pigs, and the administration of g-secretase inhibitors led to the formation of ectopic auditory hairs (Hori et al, 2007). These data suggest that Notch signaling plays an important role in limiting hair cell number.…”
Section: Discussionmentioning
confidence: 98%
“…However, in adult cochleae, no expression of Notch ligands and receptors is virtually detectable in supporting cells. For some time after damage, the temporary activation of Notch signaling is detected even in adult cochleae (Hori et al, 2007; Batts et al, 2009). The topical application of a γ-secretase inhibitor to cochleae results in the induction of hair cell (Hori et al, 2007; Mizutari et al, 2013; Tona et al, 2014a).…”
Section: Strategies For Induction Of Regenerationmentioning
confidence: 99%